PUBLIC POLICIES FOR DIGITAL INCLUSION AND INDIGENOUS PEOPLES: A BIBLIOGRAPHICAL RESEARCH - Rapôso da Silva Ferreira, Gutemberg; Tiana Cardoso Sousa, Daniele; do Socorro Silva, Maria (Revista Gênero e Interdisciplinaridade, 2023)
The goal of this article is to discuss the public policies applied to the digital inclusion of indigenous communities in Tocantins through bibliographical research, so we did a bibliography survey, made records and brought it up in the theoretical discussion. To answer the question: How can public policies through digital technologies influence indigenous communities? We used the following authors to support our research: LAKATOS (1991), ARBOS(2010), PEDROSA(2017), PINTO(2008), DE SOUZA & TOMIZAWA(2014) et al. Thus, we discuss three topics that we consider important to achieve results: Public policies for digital inclusion, Digital inclusion in indigenous communities and the digital insertion of people from Tocantins. Therefore, we came to the conclusion that two factors are important with regard to public policies for digital inclusion: education and cultural diffusion.